Propriedades termodinâmicas de misturas de biodiesel e petro-diesel em altas pressões e altas temperaturas e um novo modelo para prever o efeito da pressão na densidade - Alves, Alanderson Arthu Araújo (2022)
Reducing greenhouse gas emissions has been the main motivation to drive increased production and the participation of biofuels in the energy matrix of transport. In relation to petro-diesel, biodiesel appears as its most viable substitute so far. That said, research that report the behavior of these fuels have been intensified in the last decades. The use of biodiesel and its blends with petro-diesel can be used as fuels in existing diesel engines. However, to better predict the engine performance and seek an increase in its efficiency, the knowledge of the thermophysical properties in the face of operational variations presented are of paramount importance. In this sense, density plays an important role in the injection and combustion processes in diesel cycle engines. Thus, based on the Murnaghan equation of state, the present work reports a new model to predict the effect of pressure on the density of mixtures between petro-diesel and biodiesel, having as input data the density as a function of temperature and the volumetric composition of the components present in the mixture. Additionally, this work also presents new experimental data set for biodiesel (grape seed, corn, and linseed) + petro-diesel, at high pressure (0.10 – 100.00 MPa) and high temperature (293.15 – 413.15 K) in a composition range of 0, 20, 40, 60, 80, and 100 %v/v, totaling 1344 density data for these mixtures. Furthermore, data experiencing density was correlated with the Tammann-Tait addition connection obtaining the following thermodynamic properties: isothermal compressibility (κ_T), isobaric thermal expansibility (α_P), internal pressure (p_int) and the difference between pressure and volume heat capacities (c_p-c_v). Lastly, to test the proposed model, the experimental density data obtained in this work, together with the experimental data collected in the literature, they were submitted to tests of comparison (for validation) between the predicted value by the model and the experimental value, with smaller absolute relative deviations (% AARD) a 0,50 %, value close to the experimental uncertainty of density measurements.